2020
DOI: 10.3390/ijms21030719
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Diatom-Derived Oxylipins on the Sea Urchin Paracentrotus lividus

Abstract: Oxylipins are diatom-derived secondary metabolites, deriving from the oxidation of polyunsatured fatty acids that are released from cell membranes after cell damage or senescence of these single-celled algae. Previous results revealed harmful toxic effects of polyunsaturated aldehydes (PUAs) and hydroxyacids (HEPEs) on sea urchin Paracentrotus lividus embryonic development by testing individual compounds and mixtures of the same chemical group. Here, we investigated the combined effects of these compounds on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 64 publications
(112 reference statements)
1
18
0
Order By: Relevance
“…These results could indicate that benthic diatoms affect some common molecular pathways by changing the normal biological mechanisms, which, in turn, generate aberrant progenies in sea urchins. Interestingly, several genes followed by RT-qPCR in the present study were previously found to be functionally interconnected [41][42][43]. In particular, Varrella et al [41] showed that both diatoms altered the expression of all genes belonging to the network, except for Alix, whose relative expression was not significant (Figure 6).…”
Section: Effects Of Feeding Tests On Gene Pathwaysmentioning
confidence: 52%
“…These results could indicate that benthic diatoms affect some common molecular pathways by changing the normal biological mechanisms, which, in turn, generate aberrant progenies in sea urchins. Interestingly, several genes followed by RT-qPCR in the present study were previously found to be functionally interconnected [41][42][43]. In particular, Varrella et al [41] showed that both diatoms altered the expression of all genes belonging to the network, except for Alix, whose relative expression was not significant (Figure 6).…”
Section: Effects Of Feeding Tests On Gene Pathwaysmentioning
confidence: 52%
“…Since marine organisms are normally exposed to LOX products as a whole, very recent studies were conducted to evaluate the potentially negative effect of PUAs and HEPEs mixtures on the sea urchin P. lividus [ 74 , 76 , 78 ]. Specifically, Ruocco et al [ 76 ] showed that, by decreasing PUAs concentrations to one third of those used in individual tests (reported in Varrella et al [ 67 ]), both binary and ternary mixtures were able to induce malformations in a synergic way, with the highest percentage of malformed plutei achieved in the case of 0.5 μM DD plus 1.0 μM HD at 48 hpf.…”
Section: Detrimental Impact Of Oxylipins On Marine Invertebratesmentioning
confidence: 99%
“…The effects of oxylipin combinations on sea urchin embryos were further clarified by testing PUAs plus HEPEs mixtures [ 78 ]. Morphological observations revealed that these mixtures induced a stronger effect, compared to single compounds, with a dose-dependent developmental delay.…”
Section: Detrimental Impact Of Oxylipins On Marine Invertebratesmentioning
confidence: 99%
See 2 more Smart Citations